2015
DOI: 10.1016/j.crad.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of imaging for pulmonary embolism: too many scans or the tip of an iceberg?

Abstract: Increased detection of PE is not due to disproportionate increase in small PEs, but to increased detection of PE of all severities. This finding supports the hypothesis that PE is more common in the general population than previously appreciated, which may represent an iceberg phenomenon of previously undetected disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(10 reference statements)
0
8
0
1
Order By: Relevance
“…[33,37] Morley et al recently published a decade of single institution data finding that imaging-for PE increased 250% (>90% CTPA), PE diagnoses increased 160% and yield reduced from 24 to 20%, but the proportion of large PE was maintained. [40] They suggested that increased imaging in their institution was finding increased rates of previously undiagnosed but clinically significant PE. [40] Our study found no significant correlation for site yield or CTPA utilisation vs. the proportion of large PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33,37] Morley et al recently published a decade of single institution data finding that imaging-for PE increased 250% (>90% CTPA), PE diagnoses increased 160% and yield reduced from 24 to 20%, but the proportion of large PE was maintained. [40] They suggested that increased imaging in their institution was finding increased rates of previously undiagnosed but clinically significant PE. [40] Our study found no significant correlation for site yield or CTPA utilisation vs. the proportion of large PE.…”
Section: Discussionmentioning
confidence: 99%
“…[40] They suggested that increased imaging in their institution was finding increased rates of previously undiagnosed but clinically significant PE. [40] Our study found no significant correlation for site yield or CTPA utilisation vs. the proportion of large PE. Our data suggests that, within this regions current rates of CTPA utilisation (up to 1.5% of adult ED attenders getting CTPA) and yield, proportions of large PE seem to be maintained at historical levels.…”
Section: Discussionmentioning
confidence: 99%
“…39 With the increasing use of CTPA higher numbers of PE are being diagnosed, including both large and small PE. 23 The number of unsuspected PE being diagnosed on contrast CT of the chest performed for other reasons also supports this hypothesis. 40 There may be out-of-hospital cardiac deaths occurring that are precipitated by the haemodynamic consequences of PE in patients with undiagnosed severe coronary artery disease; however, further studies are required to investigate this.…”
Section: Discussionmentioning
confidence: 64%
“…Reported nosebleed improvements were common, though may have also been due to intervening treatment of PAVMs. 2 Conclusions Further study on the clinical efficacy and sequelae of iron treatments, and a more personalised approach to therapy, appears warranted in this patient group. Background Computed tomography of pulmonary angiogram (CTPA) is widely used for the diagnosis of patients with possible pulmonary embolism (PE).…”
mentioning
confidence: 96%
“…1 Furthermore,~1 in 20 HHT patients report that iron treatments exacerbate their nosebleeds. 2 The goal of this study was to evaluate clinical patterns of iron treatments in patients with PAVMs and HHT. Methods Iron, red cell and microbiology indices were evaluated as part of routine clinic assessments of patients with PAVMs and/or HHT.…”
mentioning
confidence: 99%